Therapeutic Potential of Shark Anti-ICOSL VNAR Domains is Exemplified in a Murine Model of Autoimmune Non-Infectious Uveitis - Kovaleva, Marina; Johnson, Katherine; Steven, John; Barelle, Caroline J.; Porter, Andrew (Frontiers in Immunology, 2017)
ABSTRACT Induced co-stimulatory ligand (ICOSL) plays an important role in the activation of T cells through its interaction with the inducible co-stimulator, ICOS. Suppression of full T cell activation can be achieved by blocking this interaction and has been shown to be an effective means of ameliorating disease in models of autoimmunity and inflammation. In this study, we demonstrated the ability of a novel class of anti-ICOSL antigen-binding single domains derived from sharks (VNARs) to effectively reduce inflammation in a murine model of non-infectious uveitis. In initial selections, specific VNARs that recognised human ICOSL were isolated from an immunised nurse shark phage display library and lead domains were identified following their performance in a series of antigen selectivity and in vitro bio-assay screens. High potency in cell-based blocking assays suggested their potential as novel binders suitable for further therapeutic development. To test this hypothesis, surrogate anti-mouse ICOSL VNAR domains were isolated from the same phage display library and the lead VNAR clone selected via screening in binding and ICOS/ICOSL blocking experiments. The VNAR domain with the highest potency in cell-based blocking assays of ICOS/ICOSL interaction was fused to the Fc portion of human IgG1 and was tested in vivo in a mouse model of interphotoreceptor retinoid-binding protein (IRBP)-induced uveitis. The anti-mICOSL VNAR Fc, injected systemically, resulted in a marked reduction of inflammation in treated mice when compared with untreated control animals. This approach inhibited disease progression to an equivalent extent to that seen for the positive corticosteroid control, Cyclosporin A, reducing both clinical and histopathological scores. These results represent the first demonstration of efficacy of a VNAR binding domain in a relevant clinical model of disease and highlight the potential of VNAR for the treatment of auto-inflammatory conditions.